1993
DOI: 10.1021/tx00036a018
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and inactivation of murine hepatic ethoxy- and pentoxyresorufin O-dealkylase by naturally occurring coumarins

Abstract: The present study was designed to evaluate the effects of a series of natural coumarins on ethoxyresorufin O-dealkylase (EROD) and pentoxyresorufin O-dealkylase (PROD) activities in vitro using hepatic tissues from SENCAR mice. Fifteen different coumarins were examined for potential modulating activities. Several naturally occurring coumarins, found in the human diet, were effective inhibitors of hepatic EROD activity in vitro, including coriandrin, bergamottin, isoimperatorin, and ostruthin. Notably, coriandr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
1
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 24 publications
4
53
1
2
Order By: Relevance
“…This observation supports previous studies that indicated that inactivation of P450 enzymes by psoralens required the presence of the furan ring double bond (Letteron et al, 1986;Cai et al, 1993). Tandem mass analysis of the glutathione conjugates of BG formed by P450 2B6 resulted in fragments that were most consistent with GS adduction to the furan ring analogous to what has been observed with 8-methoxypsoralen and P450 2B1 (Koenigs and Trager, 1998).…”
Section: Discussionsupporting
confidence: 89%
“…This observation supports previous studies that indicated that inactivation of P450 enzymes by psoralens required the presence of the furan ring double bond (Letteron et al, 1986;Cai et al, 1993). Tandem mass analysis of the glutathione conjugates of BG formed by P450 2B6 resulted in fragments that were most consistent with GS adduction to the furan ring analogous to what has been observed with 8-methoxypsoralen and P450 2B1 (Koenigs and Trager, 1998).…”
Section: Discussionsupporting
confidence: 89%
“…Angelicin, isopimpinellin, 8-methoxypsoralen, psoralen, isopsoralen, bergamottin, and other related compounds in this family have shown inhibitory effects on CYP1A1, CYP1A2, CYP2B6, CYP3A4, and CYP3A5 (Baumgart et al, 2005;Lin et al, 2005;Zhuang et al, 2013). In addition, several furanocoumarin compounds in umbelliferous vegetables, such as 8-methoxypsoralen, bergapten, and isopimpinellin, have been found to be the mechanism-based inactivators of CYP2B1 (Cai et al, 1993;Koenigs and Trager, 1998). We speculated that IMP may show a similar irreversible inhibitory effect on the CYP2B subfamily.…”
Section: Introductionmentioning
confidence: 99%
“…However, in HLMs, time-dependent CYP1A2 inhibition was only observed with the angular furanocoumarin, IPRN. This difference may be attributed to that difference in compounds although they are in the same class, different enzymes and probe P450 substrate specificity (Cai et al, 1993, Paine et al, 2004Prince et al, 2006). It remains to be seen whether the angular furanocoumarins are generally more prone to the formation of more reactive epoxide metabolites, similar to the well established Bay Region theory of polyaromatic hydrocarbons (Lehr and Jerina, 1977;Chang et al, 2013).…”
Section: Discussionmentioning
confidence: 93%